Prevalence of depressive symptoms and related factors in primary care health workers: an integrative review (Research, Society and Development, 2022)
This study aims to identify, from national and international scientific literature, the prevalence of depressive symptoms and related factors in primary health care workers. An integrative review was carried out in November 2022 in the LILACS, MEDLINE, CINAHL and Scopus databases. Initially, 2209 articles were identified, in which 14 productions were included as a sample. Evidence showed a prevalence of depressive symptoms that ranged from 11% to 55.6%. The presence of these symptoms was related to factors such as professional exhaustion, situations of violence at work and performance in the COVID-19 pandemic. The results allow the development of coping strategies for the problem. For this, it is essential to advance in the scientific field that allow a deeper understanding of the subject and its impacts on workers' health. The objective is to guarantee the attention and health promotion of these professionals, contributing to the improvement of the assistance provided by them, their quality of life and work.